Pengaruh Customer Experience Dan Customer Value Terhadap Revisit Intention Pada Agrowisata Petik Jeruk Sumbersono Dlanggu Mojokerto - Fanny Dwi Juli Muzaqqi; Lilis Sugi Rahayu Ningsih (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
The purpose of this study was to determine customer experience and customer value on revisit intention at Sumbersono Dlanggu Mojokerto Orange Picking Agrotourism. All data used in analyzing is data obtained from observation, interviews, documentation, distribution of questionnaires and various literature concerning customer experience and customer value on revisit intention at Sumbersono Dlanggu Mojokerto Orange Picking Agrotourism. This research uses quantitative methods. The population of this research is consumers who have visited as many as 100 populations, then 80 samples were taken using a purposive sampling technique. Data analysis techniques used are descriptive statistics, data quality tests, classical assumption tests, hypothesis testing and multiple linear analysis. The results showed that: 1) customer experience has a positive and significant effect on revisit intention on Sumbersono Dlanggu Mojokerto Picking Oranges Agrotourism, 2) customer value has a positive and significant effect on revisit intention on Sumbersono Dlanggu Mojokerto Picking Oranges Agrotourism, 3) customer experience and customer value has a positive and significant effect on revisit intention on Sumbersono Dlanggu Mojokerto Orange Picking Agrotourism